Novel Gyrification Networks Reveal Links with Psychiatric Risk Factors in Early Illness. (14th September 2021) - Sanfelici, Rachele; Ruef, Anne; Antonucci, Linda A; Penzel, Nora; Sotiras, Aristeidis; Dong, Mark Sen; Urquijo-Castro, Maria; Wenzel, Julian; Kambeitz-Ilankovic, Lana; Hettwer, Meike D; Ruhrmann, Stephan; Chisholm, Katharine; et al.
Abstract: Adult gyrification provides a window into coordinated early neurodevelopment when disruptions predispose individuals to psychiatric illness. We hypothesized that the echoes of such disruptions should be observed within structural gyrification networks in early psychiatric illness that would demonstrate associations with developmentally relevant variables rather than specific psychiatric symptoms. We employed a new data-driven method (Orthogonal Projective Non-Negative Matrix Factorization) to delineate novel gyrification-based networks of structural covariance in 308 healthy controls. Gyrification within the networks was then compared to 713 patients with recent onset psychosis or depression, and at clinical high-risk. Associations with diagnosis, symptoms, cognition, and functioning were investigated using linear models. Results demonstrated 18 novel gyrification networks in controls as verified by internal and external validation. Gyrification was reduced in patients in temporal-insular, lateral occipital, and lateral fronto-parietal networks (p FDR  < 0.01) and was not moderated by illness group. Higher gyrification was associated with better cognitive performance and lifetime role functioning, but not with symptoms. The findings demonstrated that gyrification can be parsed into novel brain networks that highlight generalized illness effects linked to developmental vulnerability. When combined, our study widens the window into the etiology of psychiatric risk and its expression in adulthood.